1999
DOI: 10.1046/j.1469-8137.1999.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon gain in a multispecies canopy: the role of specific leaf area and photosynthetic nitrogen‐use efficiency in the tragedy of the commons

Abstract: Models have been formulated for monospecific stands in which canopy photosynthesis is determined by the vertical distribution of leaf area, nitrogen and light. In such stands, resident plants can maximize canopy photosynthesis by distributing their nitrogen parallel to the light gradient, with high contents per unit leaf area at the top of the vegetation and low contents at the bottom. Using principles from game theory, we expanded these models by introducing a second species into the vegetation, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 38 publications
10
129
0
3
Order By: Relevance
“…NS = not significant potential, also enable them to compete more effectively for light (Schieving and Poorter 1999). Indeed Joshi and Vrieling (2005) found that invasive J. vulgaris plants produced significantly higher biomass and had 37 % higher reproductive output compared to native plants in a common garden experiment after 8 months growth.…”
Section: Growth Traits and Tolerancementioning
confidence: 99%
“…NS = not significant potential, also enable them to compete more effectively for light (Schieving and Poorter 1999). Indeed Joshi and Vrieling (2005) found that invasive J. vulgaris plants produced significantly higher biomass and had 37 % higher reproductive output compared to native plants in a common garden experiment after 8 months growth.…”
Section: Growth Traits and Tolerancementioning
confidence: 99%
“…In contrast, tall species can compete for light during the whole growing season and should therefore be affected similarly by additional shading in early or late season. Shading in late season might even affect tall species more than short species because the investment in tall supporting structures and large leaf area might not pay off if the whole plant suddenly becomes shaded (Henry and Aarssen 1997;Schieving and Poorter 1999). However, these seasonal effects have not yet been demonstrated experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Foster and Gross 1998;Jensen and Schrautzer 1999;Zobel 2001), though few studies have directly investigated how species coexistence in grasslands depends on light availability. In dense and tall vegetation, light limitation is caused by the plant canopy itself, which creates a vertical light gradient (Hirose and Werger 1995;Anten and Hirose 1999;Schieving and Poorter 1999). The persistence of species in the lower canopy layers depends on their ability to tolerate low-light conditions, or to grow during periods with greater light availability (Yoshie 1995;Stuefer and Huber 1998).…”
Section: Introductionmentioning
confidence: 99%
“…de N orgânico expressado por unidade de AF (Schieving & Poorter 1999). Segundo Garnier et al (1995), a eficiência pela qual uma espécie utiliza N para crescer, ou seja, uma correlação positiva entre REN e AFE, se dá pelos seguintes aspectos: diferenças entre as espécies na absorção da luz nas folhas, variações na proporção de compostos de N orgânico alocado pela fotossíntese, funções não fotossintéticas, diferenças nos tempos de assimilação de CO 2 por unidade de N fotossintético, diferenças na quantidade de fotorespiração e pelas diferenças no conteúdo de N por unidade de AF.…”
Section: Resultsunclassified